2023
DOI: 10.1145/3561820
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty-Aware Personal Assistant for Making Personalized Privacy Decisions

Abstract: Many software systems, such as online social networks enable users to share information about themselves. While the action of sharing is simple, it requires an elaborate thought process on privacy: what to share, with whom to share, and for what purposes. Thinking about these for each piece of content to be shared is tedious. Recent approaches to tackle this problem build personal assistants that can help users by learning what is private over time and recommending privacy labels such as private or public to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…For instance, participants understand better why images have been identified as public (𝑀 = 4.1, 𝑆𝐷 = 1.2). This is inline with recent work [3], which has shown that privacy is inherently ambiguous and their personal privacy assistant yields better performance for the public class.…”
Section: Interval Levelsupporting
confidence: 88%
See 4 more Smart Citations
“…For instance, participants understand better why images have been identified as public (𝑀 = 4.1, 𝑆𝐷 = 1.2). This is inline with recent work [3], which has shown that privacy is inherently ambiguous and their personal privacy assistant yields better performance for the public class.…”
Section: Interval Levelsupporting
confidence: 88%
“…Their proposed system performs well in predicting privacy, even though the personal assistant only has access to a small amount of data. Ayci et al [3] propose a personal privacy assistant called PURE to preserve the privacy of its user. PURE is aware of uncertainty by generating an uncertainty value for each prediction of a given image, informing its user about it, and delegating decisions back to the user if it is uncertain about its predictions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations